Contact lens fitting in keratoconus – a prospective study on visual and functional outcomes - Das, Seema; John, Bina; Mohan, Sujatha; Rajan, Mohan; K., Anantalaxmi (International Journal of Research in Medical Sciences, 2017)
Background: Contact lenses continue to play an important role in the effective management of keratoconus. To report visual and functional outcomes of various types of contact lenses in keratoconus patients at a tertiary referral centre. Methods: Study design: Prospective Cohort Study. 100 eyes of 51 patients with keratoconus were fitted with contact lenses with follow up at one and six months and evaluated. Statistical analysis: Paired t test, Chi Square test. Results: Best contact lens corrected visual acuity was better than best spectacle corrected visual acuity (p= 0.000).78 % patients were fitted with RGP, 12% with Rose K, 6 % Soft, 2% Piggy Back and 2% with Kerasoft IC lenses. Soft lens were preferred in mild keratoconus, RGP for moderate and Rose K, Piggy Back and Kerasoft IC lenses for severe keratoconus. The mean daily wear among the lenses was 7.59 hours per day with Rose K lenses having maximum wearing time of 8.33 hours. Comfort and tolerance level was maximum in Rose K, Piggy Back, Kerasoft IC and RGP lens users whereas it was less in the soft lens group. No significant complications were noted with contact lens use. Conclusion: Contact lenses continue to play an important role in the effective management of keratoconus. With the advent of newer designs of contact lenses for keratoconus it is possible to customize the lenses to optimize patient’s requirement visually and functionally.